The The Effect of Foot Soaking Therapy With Warm Ginger Water on Blood Pressure Reduction In Hypertensive Patients - Nurlintang, Dewi; Setyawati, Retno (Journal of Smart Nursing and Health Science, 2026)
Background: Hypertension is one of the major health problems whose prevalence continues to increase and contributes significantly to the incidence of cardiovascular disease. In addition to pharmacological therapy, a safe, easy-to-implement, and locally-based non-pharmacological approach is needed. One complementary therapy with potential is warm ginger foot bath therapy, which is believed to improve blood circulation and lower blood pressure. This study aims to analyse the effect of warm ginger foot bath therapy on blood pressure reduction in hypertensive patients. Method: This study used a quasi-experimental design with a pretest and posttest approach on hypertensive patients undergoing treatment at Sari Asih Hospital in Ciledug, Tangerang. The intervention, in the form of a warm ginger foot bath, was carried out routinely according to established procedures. Blood pressure was measured before and after the intervention using standard measuring equipment. Results: The results showed a decrease in blood pressure after the warm ginger foot bath therapy. This therapy provided relaxation, vasodilation of blood vessels, and improved peripheral circulation, which contributed to blood pressure control. Conclusion: The conclusion of this study indicates that warm ginger foot bath therapy has an effect on.